Dampak Teknologi Informasi Terhadap Identitas Lokal Masyarakat Melayu Riau - Sari, Delsi Lina; Ziulhaq, Ziulhaq; Khotimah, Khusnul; Susanto, Susanto; Mustikawati, Rina (Multiverse: Open Multidisciplinary Journal, 2023)
The advancement of technology and information has brought about both positive and negative consequences for the local identity of the Malay community. This study aims to assess the influence of information technology on the local identity of the Malay community, employing a literature review methodology. Findings reveal significant impacts of information technology on the identity of the Riau Malay Community, particularly evident in language and communication patterns, traditional attire, and cultural demeanor. To address these impacts, solutions include implementing digital culture education, reinforcing digital identity, and enacting cultural protection regulations. These measures aim to preserve and promote the unique cultural heritage of the Malay community in the face of technological advancement, ensuring its continuity and relevance in the digital age.